Ca2+-stimulated ADCY1 and ADCY8 regulate distinct aspects of synaptic and cognitive flexibility - Zhang, Ming; Wang, Hongbing (Frontiers in Cellular Neuroscience, 2023)
The type 1 and 8 adenylyl cyclase (ADCY1 and ADCY8) exclusively account for Ca 2+stimulated cyclic AMP (cAMP) production and regulate activity-dependent synaptic modification. In the present study, we examined distinct forms of synaptic plasticity in the hippocampus of Adcy1 -/and Adcy8 -/mice. We found that, at the Schaffer collateral-CA1 synapses, while the Adcy8 -/mice displayed normal long-term potentiation (LTP) following various induction protocols with high frequency stimulation (HFS), the Adcy1 -/mice showed protocol-dependent deficits in LTP. We also found that long-term depression (LTD) requires ADCY1 but not ADCY8. Interestingly, both Adcy1 -/and Adcy8 -/mice showed defective synaptic depotentiation (i.e., activity-dependent reversal of LTP); the deficits in Adcy8 -/mice were dependent on the induction protocol. Examination of spatial memory found that ADCY1 is required for the formation of both initial and reversal memory. ADCY8 is only required for reversal memory formation. These data demonstrate that ADCY1 and ADCY8 play distinct roles in regulating synaptic and cognitive flexibility that involves bidirectional modification of synaptic function.